PENGARUH BRAND AMBASSADOR DAN BRAND IMAGE ERIGO TERHADAP MINAT BELI PADA APLIKASI TIKTOK: PENGARUH BRAND AMBASSADOR DAN BRAND IMAGE ERIGO TERHADAP MINAT BELI PADA APLIKASI TIKTOKSHOP - Satria Novaldy Wibowo,; Saino, Saino (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
Advances in information technology, especially the internet, have driven significant changes in various fields, including digital marketing through social media. Platforms such as TikTok are now strategic tools to reach consumers. One example of utilizing this strategy is Erigo, which uses brand ambassadors and brand image to increase consumer buying interest. This study aims to analyze the influence of Erigo's brand ambassadors and brand image on TikTok users' purchase intention. With a quantitative approach, this study involved university students in Surabaya as the population, using questionnaires as data collection instruments. Data analysis was conducted through multiple linear regression with the help of SPSS software. The results showed that both brand ambassador and brand image have a significant influence on buying interest in TikTok